Experimental study of the influence of hypercholesterin diet on the lower jaw follicles in mice embryos - Kuz’mina, V.; Yakubova, I. (Actual Dentistry, 2018)
Resume. One of the factors that leads to a violation of the physiological development of all organs and systems of the fetus is the inappropriate nutrition of pregnant women in a quantitative and qualitative ratio. Violation of odontogenesis in the antenatal period is possible both in the phase of formation of the protein matrix and in the phase of primary mineralization. The Aim of this Work was to study the influence of nutrients (2 %) Cholesterol on the morphological structure of the dental follicles in mice embryos at the stage of histogenesis. Materials and methods of research. For the study were used white, unborn mice weighing 25–28 g (40 animals). The females of the control group received a diet of vivarias, and females of the experimental group – a feed with high Cholesterol content. The material for the study was the lower jaw of the 17–18 day embryos of mice. Results and discussion. As a result of the morphological study of the dental follicles of the 17–18 day embryos of mice of the experimental group there were identified the following morphological changes: odonotoblasts with different forms, their processes are poorly formed or absolutely absent, thinning of the dentin layer and its in homogeneity, the absence of a clear boundary on the level between the mantle dentin and circumpulpal dentin, forming in the form of a wavy or «broken» line; absence of vacuolar inclusions in the enameleoblastic cytoplasm. Conclusions. Thus, we have received confirmation of the negative influence of excessive amount of fats in the diet of the pregnant woman on the initiation and primary mineralization of hard tissues of the teeth in fetus. Key words: lower jaw of the mouse embryo, odontoblasts, enameloblasts, dental follicle.